El posicionamiento en el mercado en relación con el crecimiento económico de la empresa alpiwater del cantón Piñas. - Pullas Tinoco, Tania Priscila (2017)
Ecuador has 14,483,499 inhabitants, according to the National Institute of Statistics and Censuses (INEC) that is the information that resulted from the Census of Population and Housing that took place on November 28, 2010. Within the same census the way was determined in which The inhabitants of the country consume water in their homes and the percentages found are: 41.8% consume purified water, 30.2% boil it in their homes, 24.4% drink it as it arrives at home, 2.5% put chlorine and 1.2% filter it. According to the aforementioned, it was determined the importance of the analysis of a company that provides purified water of quality in the medium to promote the consumption of the same one since the human being needs to consume the best quality water and thus we will maintain a balance in Our organism and avoid diseases. In the Province of El Oro, there are several companies of purification, packaging and distribution of water in the different cantons. For this title work we have taken to the Company ALPIWATER of the Canton Piñas, analyzing the approach of the positioning in the market in relation to the economic growth, to offer a greater development to this company. The methodology that was carried out to carry out this research is through an integrative project, which implies a research process aimed at exploring in a profound and dynamic way the object of study; Important data regarding the subject were also included, taking them from authoritative scientific journals as theoretical bases of research. Another instrument that was used during the development of this work was the application of surveys which were carried out initially with the taking of the sample size to determine the number of people to be performed, as a next step the formulation of the question bank, under The answers obtained were able to extract the necessary information to carry out our research project. The main objective of the present work is the analysis of the level of positioning in the market in relation to the economic growth of the company ALPIWATER of Canton Piñas, the result obtained from the investigation is that it is indispensable to remain in the minds of the consumers and a form To do so is to offer a quality product that provides customer satisfaction. The purification process used by the Company ALPIWATER is one of the most used by the companies of great prestige in the medium which is of reverse osmosis, this is a technique of separation of particles, metals and salts of water. Another important process is the packaging which is given by the use of machines of the latest technology, so that the contamination of the water with the environment does not occur. The ALPIWATER Company of the Canton Piñas has the characteristics requested by the consumers in the survey, for which it was determined that different strategies must be carried out through the implementation of a suitable system with publicity and promotions to make known the brand and the Instead, encourage the client to take over the company.